Preterm Delivery and Long-Term Mortality in Women: National Cohort and Co-sibling Study. Issue 2 (24th June 2021) - Crump, C.; Sundquist, J.; Sundquist, K.
Abstract : ( BMJ . 2020;370:m2533) Preterm birth has been associated with numerous health risks to both the mother and child. Women who deliver prematurely (gestational age of <37 wk) may have increased risk of heart disease and other cardiometabolic disorders later in life. Yet, information on the long-term impact of premature delivery on mortality and the ultimate underlying causes of death is limited. The aim of this study was to determine the association between preterm delivery and the long-term mortality risk among women who deliver prematurely.